Increased risk of endotracheal intubation and heart failure following acute myocardial infarction in patients with urolithiasis: a nationwide population-based study - Lin SK; Liu JM; Chang YH; Ting YT; Pang ST; Hsu RJ; Lin PH (Dove Medical Press, 2017)
Shun-Ku Lin,1,2,* Jui-Ming Liu,3,* Ying-Hsu Chang,4 Yuan-Tien Ting,5 See-Tong Pang,4 Ren-Jun Hsu,6–8 Po-Hung Lin4,9 1Institute of Traditional Medicine, School of Medicine, National Yang-Ming University, 2Department of Chinese Medicine, Taipei City Hospital, Ren-Ai Branch, Taipei, 3Division of Urology, Department of Surgery, Taoyuan General Hospital, Ministry of Health and Welfare, 4Division of Urology, Department of Surgery, Chang Gung Memorial Hospital at Linkou, Taoyuan, 5Division of Urology, Department of Surgery, Chang Bing Show Chwan Memorial Hospital, Changhua, 6Biobank Management Center of the Tri-Service General Hospital, 7Department of Pathology and Graduate Institute of Pathology and Parasitology, the Tri-Service General Hospital, 8Graduate Institute of Life Sciences, National Defense Medical Center, Taipei, 9Graduate Institute of Clinical Medical Science, College of Medicine, Chang Gung University, Taoyuan, Taiwan, Republic of China *These authors contributed equally to this work Background: Urolithiasis is a common urinary tract disease worldwide. It has been connected to systemic diseases, including hypertension, diabetes mellitus, metabolic syndrome, and cardiovascular disease. In the current study, we aimed to evaluate the relationship between urolithiasis and the complications of acute myocardial infarction (AMI). Materials and methods: Data were obtained from the Longitudinal Health Insurance Database 2005 of the National Health Insurance Research Database. All AMI cases, both those who were hospitalized and those who were treated in the emergency department, were identified using the International Classification of Diseases, ninth revision, Clinical Modification (ICD-9-CM) code. Results: A total of 37,052 patients with urinary calculi and 148,209 control subjects were enrolled in this study. The average follow-up period was 9.51 years. The risk of AMI was higher among patients with urolithiasis (adjusted hazard ratio [aHR] 1.07, 95% confidence interval [95% CI] 1.03–1.13). We detected a significant association between urolithiasis and intubation (aHR 1.53, 95% CI 1.36–1.73), intensive care unit treatment (aHR 1.22, 95% CI 1.13–1.32), heart failure (aHR 1.59, 95% CI 1.42–1.78), shock (aHR 1.53, 95% CI 1.32–1.77), and arrhythmias (aHR 1.18, 95% CI 1.06–1.33). Furthermore, certain medical treatments for urolithiasis were found to be related to myocardial infarction (MI). Nonsteroidal anti-inflammatory drugs (NSAIDs) were significantly associated with a high risk of AMI. In contrast, allopurinol, thiazide diuretic, potassium-sparing diuretics, and a-blockers have negative association with AMI. Conclusion: Urolithiasis had a significantly increased risk of endotracheal intubation and heart failure following AMI. In addition, urolithiasis was also associated with a high risk of intensive care unit treatment, shock, and arrhythmias after AMI. Medical treatments for urolithiasis may decrease the risk of MI, except the use of NSAIDs. Keywords: urolithiasis, renal calculi, acute myocardial infarction, National Health Insurance Research Database, endotracheal intubation, heart failure